Total Synthesis of Anticancer Pacharin, Bauhiniastatin 4, and Bauhinoxepins C and D - Sang-aroon, Pattarapon; Boosaman, Norasian; Rakchaya, Intouch; Siri, Wiradet; Tieojaroenkit, Asamaporn; Chuanopparat, Nutthawat; Ngernmeesri, Paiboon (Synthesis, 2025)
Reported herein is the total synthesis of anticancer pacharin, bauhiniastatin 4, and bauhinoxepins C and D. The synthetic strategy features a cascade reaction involving intermolecular nucleophilic aromatic substitution followed by intramolecular Knoevenagel condensation to form a dibenzo[b,f]oxepine scaffold of these compounds. Pacharin and bauhiniastatin 4 were synthesized in eight steps from 2-methylresorcinol with overall yields of 5.4% and 8.3%, respectively. Similarly, bauhinoxepins C and D were synthesized in seven steps with overall yields of 3.5% and 2.6%, respectively. This methodology offers an efficient route for accessing these natural products with implications for medicinal and synthetic chemistry.
Keywords: natural product synthesis; cascade reaction; dibenzo[b,f]oxepines; anticancer agents; nucleophilic aromatic substitution; Knoevenagel condensation